2020
DOI: 10.1101/2020.09.10.290825
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phosphodiesterase Type 4 anchoring regulates cAMP signaling to Popeye domain-containing proteins

Abstract: Cyclic AMP is a ubiquitous second messenger used to transduce intracellular signals from a variety of Gs-coupled receptors. Compartmentalisation of protein intermediates within the cAMP signaling pathway underpins receptor-specific responses. The cAMP effector proteins protein-kinase A and EPAC are found in complexes that also contain phosphodiesterases whose presence ensures a coordinated cellular response to receptor activation events. Popeye proteins are the most recent class of cAMP effectors to be identif… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…It is unlikely that the impaired regulation of TREK-1 alone is sufficient to explain the strong phenotype of the Popdc1 and -2 null mutants, particularly when compared to phenotypes of Kcnk2 or Adcy9 deletions in mice. Recently, an interaction of POPDC1 and PDE4 isoforms have been described ( 54 ). A cell-permeable peptide that disrupts the POPDC1:PDE4 complex caused a reduction in cycle length of spontaneous Ca 2+ transients in mouse SA nodes.…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that the impaired regulation of TREK-1 alone is sufficient to explain the strong phenotype of the Popdc1 and -2 null mutants, particularly when compared to phenotypes of Kcnk2 or Adcy9 deletions in mice. Recently, an interaction of POPDC1 and PDE4 isoforms have been described ( 54 ). A cell-permeable peptide that disrupts the POPDC1:PDE4 complex caused a reduction in cycle length of spontaneous Ca 2+ transients in mouse SA nodes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Tibbo et al (2020) showed that POPDC1 proteins, similar to other cAMP effectors, also form a complex with PDE4s, particularly and preferably with the PDE4A isoform [111]. The study concluded that POPDC1-PDE4A complex formation serves as a protective measure, which prevents inappropriate cAMP binding to the Popeye domain under basal conditions.…”
Section: Popdc Proteins and Cardiac Arrhythmiasmentioning
confidence: 97%
“…The study concluded that POPDC1-PDE4A complex formation serves as a protective measure, which prevents inappropriate cAMP binding to the Popeye domain under basal conditions. Experimentally orchestrated disruption of PDE4 and POPDC1 interaction resulted in a decreased interaction between POPDC1 and TREK1 as well as causing a prolongation of AP duration in isolated ventricular myocytes [111].…”
Section: Popdc Proteins and Cardiac Arrhythmiasmentioning
confidence: 99%
See 2 more Smart Citations